THE IDENTIFICATION OF THE MAIN GRAMMATICAL AND SEMANTIC FEATURES OF THE LIGHT OR DEFECTED VERB " BÖN" IN KURDISH LANGUAGE (BADINAN ACCENT) .: (كارێ بێهێزێ بونەتيا(د گوڤەرا بەهدينيدا - Ahmed, Bayez Omer; Ali, Viyan Ibrahim (Journal of Duhok University, 2018)
The kurdish Copular light verb "bön" (to be) is often confused with the resultative copular verb "bö" (become) as both of them have the same phonological base form.This research paper is an attempt to identify the main grammatical and semantic features  of  the light or defected verb " bön" and the types of complements this verb subcategorizes for.The research is  an emperical investigation to find scientific  and convincing  answers to the following questions:1- What are the defining characteristics of alight verb in kurdish?2- Howmany light verbs exist in kurdish?3- Howmany tenses are realized by the light verb?4-  Does the type and position of the complement indicate the state of the verb as being light?To answer these quastions, the researchers investigated the features of  the light verb in kurdish in relation to tense and modality, and also the types of complemention. It is noted that  the light verb in kurdishIs not inflected for all tenses and   mood, and also the position of complementation  is adecisive factor.